Expression of Political Friends AhokVoluntarism in Elections Jakarta 2017 - Iradhad Taqwa (Journal of Local Government Issues (LOGOS), 2018)
Volunteer group is one of the associations of community's political articulation in the electoral moment. By campaigning independence, non-partisan in nature, and moving in a collective way are proven able to make the volunteer group as an alternative actor and significant political force in mobilizing support and voice. Volunteer group Teman Ahok (Friends of Ahok) is a movement that openly declared itself as the political volunteer with political aims as an additional element in the winning of candidate pair Basuki Tjahaya Purnama (BTP) and Djarot Saiful Hidayat in the 2017 Jakarta gubernatorial election.  The appearance of Teman Ahok in the political arena of the 2017 Jakarta gubernatorial election is related to the BTP's populism figure. Quick changes in political escalation force Teman Ahok to change its position and political role. That fluctuation brings an important dynamic to the Teman Ahok journey. It is interesting to observe Teman Ahok activity in compile community participant and then aggregate it since it causes a public perception that is diametrically opposed at a time; supporting & not supporting. This writing will analyze the expression of Teman Ahok political voluntarism and will assess the significant benefit resulted in during the process of electoral democracy.